(
3
x
3
2
y
3
x
2
y
−
1
2
)
−
2
(
3
x
3
2
y
3
x
2
y
-
1
2
)
-
2
Move
x
3
2
x
3
2
to the denominator using the negative exponent rule
b
n
=
1
b
−
n
b
n
=
1
b
-
n
.
⎛
⎝
3
y
3
x
2
y
−
1
2
x
−
3
2
⎞
⎠
−
2
(
3
y
3
x
2
y
-
1
2
x
-
3
2
)
-
2
Multiply
x
2
x
2
by
x
−
3
2
x
-
3
2
by adding the exponents.
Tap for more steps...
(
3
y
3
x
1
2
y
−
1
2
)
−
2
(
3
y
3
x
1
2
y
-
1
2
)
-
2
Move
y
−
1
2
y
-
1
2
to the numerator using the negative exponent rule
1
b
−
n
=
b
n
1
b
-
n
=
b
n
.
(
3
y
3
y
1
2
x
1
2
)
−
2
(
3
y
3
y
1
2
x
1
2
)
-
2
Multiply
y
3
y
3
by
y
1
2
y
1
2
by adding the exponents.
Tap for more steps...
⎛
⎝
3
y
7
2
x
1
2
⎞
⎠
−
2
(
3
y
7
2
x
1
2
)
-
2
Change the sign of the exponent by rewriting the base as its reciprocal.
⎛
⎝
x
1
2
3
y
7
2
⎞
⎠
2
(
x
1
2
3
y
7
2
)
2
Use the power rule
(
a
b
)
n
=
a
n
b
n
(
a
b
)
n
=
a
n
b
n
to distribute the exponent.
Tap for more steps...
(
x
1
2
)
2
3
2
(
y
7
2
)
2
(
x
1
2
)
2
3
2
(
y
7
2
)
2
Simplify the numerator.
Tap for more steps...
x
3
2
(
y
7
2
)
2
x
3
2
(
y
7
2
)
2
Simplify the denominator.
Tap for more steps...
x
9
y
7
Answer:
5a^2 +2a
Step-by-step explanation:
Like terms are ones with the same exponent of x. They can be combined.
3a^2 +2a +2a^2
= (3a^2 +2a^2) +2a
= (3+2)a^2 +2a
= 5a^2 +2a
4x-5y=3
4x-5(10)=3
4x-50=3
+50 +50
4x=53
/4 /4
x=53/4
Hdbsjzghsbnshhsjjgshsghsbs snags is dispatched shjahshsnshshs shhshshsgstshsbabanja nkowoodpupouodkenwbw wgarhabssbs